2016
DOI: 10.15359/mhs.12-2.3
|View full text |Cite
|
Sign up to set email alerts
|

Nivel de actividad física habitual en escolares de 8-9 años de España e India

Abstract: ResumenEl nivel de actividad física de las personas es un tema prioritario a escala internacional. Sobre este tema, el objetivo del presente artículo fue analizar y comparar el nivel de actividad física habitual de escolares de 8-9 años de la región de Murcia, España y el Distrito de Karbi Anglong, Assam en India. Para ello, se administró el cuestionario PACE (Physician-based Assessment and Counseling for Exercise) a un total de 85 escolares (44 de España y 41 de India). Los resultados evidenciaron que la mues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
5
0
3
Order By: Relevance
“…However it is also clear that the physical activity they do is not enough, according to WHO recommendations, as it has been indicated in the studies by Romero et al (2008), Martínez-Gómez et al (2009), García-Cantó (2011) and López et al (2016a, b, c, d). Therefore, according to recent studies, Spanish schoolchildren do physical activity, but not enough.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However it is also clear that the physical activity they do is not enough, according to WHO recommendations, as it has been indicated in the studies by Romero et al (2008), Martínez-Gómez et al (2009), García-Cantó (2011) and López et al (2016a, b, c, d). Therefore, according to recent studies, Spanish schoolchildren do physical activity, but not enough.…”
Section: Introductionmentioning
confidence: 98%
“…Physical activity is also very beneficial in people with special needs, such as individuals with Down syndrome (López-Sánchez and López-Sánchez 2013) and schoolchildren with ADHD (López-Sánchez et al 2014, 2015a, b, d, e, 2016a, b, c, d), and can improve health parameters such as physical fitness, body image, heart rate, blood pressure, body fat, general and segmentary motor coordination, sleep quality and life quality.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, PA declines dramatically during this period [7], [8] and [1]. This is also observed in more recent research as well [16] and [17]. The fall could be more pronouced in the developing societies where students seem to face much pressure due to fear of future unemployment.…”
Section: Introductionmentioning
confidence: 62%
“…Such issues of adolescent in the context of gender disparity persisted in a typical developing society are still under-researched in the existing literature. In a very resent study, López Sánchez et al [16] tried to estimate the level of habitual physical activity in children and adolescents from the Region of Murcia (Spain) using a questionnaire on Physician-based Assessment and Counselling for Exercise (PACE) among 1055 children and adolescents (532 males and 523 females), aged between 3 and 18 years. They found that the samples were not engaged in sufficient level of physical activity in comparison with the desired level, according to the recommendations of the World Health Organization.…”
Section: Introductionmentioning
confidence: 99%
“…Igualmente, en una investigación realizada por Meseguer (15) en Murcia (España), se evaluó la AF realizada por adultos en relación con el tiempo libre, los resultados demostraron que las personas jóvenes realizan AF vigorosa. Otro estudio, realizado en Costa Rica por López (16) años, con lo que se comprobó que con la edad disminuye la práctica de la AF. En relación con el sexo, se evidenció que en dos de las instituciones los niños tienen un nivel más elevado de AF en comparación con las niñas; en la otra, el comportamiento frente al NAF general es similar en niños y niñas.…”
Section: Discussionunclassified